2019
DOI: 10.1017/ice.2019.108
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance patterns of urine culture specimens from 27 nursing homes: Impact of a two-year antimicrobial stewardship intervention

Abstract: Objective:Identify changes in the prevalence and antimicrobial resistance patterns of potentially pathogenic bacteria in urine cultures during a 2-year antimicrobial stewardship intervention program in nursing homes (NHs).Design:Before-and-after intervention study.Setting:The study included 27 NHs in North Carolina.Methods:We audited all urine cultures ordered before and during an antimicrobial stewardship intervention. Analyses compared culture rates, culture positive rates, and pathogen antimicrobial resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…The findings of this study showed that E. coli was the most commonly identified pathogen, which was in line with the findings of previous studies, such as that by Tandan et al. 10 in which E. coli was found to be the commonest UTI-causing organism. In addition, Gessese et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings of this study showed that E. coli was the most commonly identified pathogen, which was in line with the findings of previous studies, such as that by Tandan et al. 10 in which E. coli was found to be the commonest UTI-causing organism. In addition, Gessese et al.…”
Section: Discussionsupporting
confidence: 93%
“…The second most common uropathogen identified in our study was Staphylococcus species. The findings of the antimicrobial resistance profile are supported by the findings of numerous previous studies 5 , 10 showing that Staphylococcus species are highly resistant gram-negative bacteria. In addition, most isolated gram-negative bacteria are sensitive to gentamicin, ceftazidime, and ciprofloxacin whereas these bacteria are resistant to ampicillin, chloramphenicol, and amoxycillin.…”
Section: Discussionsupporting
confidence: 75%
“…Nevertheless, it is very difficult to determine the original source of transmission in this population. The crucial role of care homes in the transmission of MDRO infections has been consistently reported [13][14][15][16]. A number of factors could explain this high transmission, e.g., healthcare personnel simultaneously working in several care homes, the high rate of hospitalization and antibiotic use in this vulnerable population, or a lack of resources and training in infection prevention measures, as previously suggested in Spain [17].…”
Section: Discussionmentioning
confidence: 75%
“…Although the aforementioned review did not show conclusive results regarding the usefulness of strategies to reduce AMR in care homes [14], some evidence shows promising results. For instance, a recent antimicrobial stewardship intervention for older people in nursing homes conducted in North Carolina significantly reduced urine culture positive MDRO rates [16]. Based on these facts, it seems clear that nursing homes, care homes and long-stay residences should be considered in addition to hospitals when planning regional and national infection control strategies to reduce AMDR.…”
Section: Introductionmentioning
confidence: 99%
“…These results are similar to common pathogens reported from either UTI or urine cultures from nursing home residents in other studies. 4,[14][15][16][17][18] Within nursing homes, levels of antibiotic resistance, including MDR, were generally higher among the CA-SUTI events than UTIs not associated with catheters, most notably for vancomycin resistance in E. faecium and extended-spectrum cephalosporin and carbapenem resistance in Klebsiella spp. These differences observed among nursing-home UTI event types may be explained by the role that biofilm formation on indwelling devices plays in the selection and emergence of antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%